Diversification strategies have a stabilizing effect for income and food availability during livelihood shocks: Evidence from small-scale aquaculture-agriculture systems in Myanmar during the COVID-19 pandemic - Wang, Quanli; Rossignoli, Cristiano; Brako Dompreh, Eric; Su, Jie; Griffiths, Don; Htoo, Khaing; Nway, Hsu Myat; Akester, Michael; Gasparatos, Alexandros (Elsevier Masson, 2024)
CONTEXT: Diversification is an important strategy used by millions of small-scale food producers globally to improve yields, farm profitability, and food security. Diversification can also enable small-scale producers to cope better with livelihood shocks. However, it is not always clear through which pathways diversification practices can stabilize livelihoods and food security in small-scale production systems, especially in the context of the recent COVID-19 pandemic. OBJECTIVE: In this study we examined whether and how diversification practices stabilized income and food availability in small-scale food production systems during the COVID-19 pandemic. The diversification practices explored in this study included fish polyculture and integrated aquaculture-agriculture (IAA), and their combination. We compared small-scale systems employing different combinations of these diversification strategies, with systems that did not contain them. METHODS: We analyzed 300 surveys of small-scale aquaculture producers in Myanmar. Structural equation modeling was applied to examine the multivariate relationships between the adoption of diversification practices among the small-scale producers, and whether and how the adoption stabilized their livelihoods during the COVID-19 pandemic in Myanmar. RESULTS AND CONCLUSIONS: We find that the integration of diversification practices in different small-scale aquaculture-agriculture (SSAA) production systems had generally positive effects for the stabilization of income, food availability or both during the COVID-19 pandemic. The novelty of the study is the unraveling of the differentiated pathways between production models that enabled these stabilization processes emerge. We find major divergences in the stabilization potential between polyculture and IAA, both in terms of the magnitudes of the stabilization effects and the pathways. Polyculture generally offered more significant stabilizing effects than IAA. Surprisingly the highest and more significant positive effects for the stabilization of food availability came through the purchase of food items from extra fish/crop income, rather than their increased self-consumption. SIGNIFICANCE: Overall, the SSAA production systems combining different diversification practices could form proactive strategies to help small-scale food producers cope with livelihood shocks.